Perception of biological risk and food choices in university students in Naples (Italian Journal of Public Health, 2005)
The aim of the present survey was to assess the perceived risk of foodborne infections in young adults witha high education level. The authors investigated their knowledge of foodborne infections, the preparationand storage of food that favour these infections and the rules of food safety and hygiene for consumerprotection, as well as their behaviour regarding personal hygiene and their eating habits outside the home.The results showed that they had a good level of knowledge across all of the fields investigated, but outsidethe home they tended to favour food products that have a high risk of foodborne infection.This confirms that lifestyle and eating habits are strongly influenced by socio-economic factors, fashion, themedia and by the market demands of the food industry.
Keywords: foodborne infections; food safety; eating habits